Coherence and grounding in discourse : outcome of a symposium, Eugene, Oregon, June 1984 - Tomlin, Russell S. (Typological studies in language, 1987)
This volume seeks to expand our understanding of the relation holding between discourse relations, cognitive units, and linguistic coding. The twenty contributions in this collection explore one or more of the following themes: How point of view, or the salience of information in discourse, affects the organizational coherence of text and discourse; the concept of cognitive and linguistic event and how events are reflected in text and discourse organization; the nature of linguistic coding of events and other kinds of significant information; and the cognitive bases or cognitive correlates of.